Decoding of DVB-T2 signals for co-existing applications - Lim, Flora Liyi (2019)
DVB-T2 (Digital Video Broadcasting – Second Generation Terrestrial) is an extension of the television standard DVB-T for the transmission of digital terrestrial television. It provides higher efficiency, robustness and flexibility for audio, video, and data services for fixed, portable, and mobile devices. The aim of this research is to focus on the decoding of DVB-T2 signals for co-existing purposes. This research starts with studying the overall DVB-T2 system architecture. It continues with investigation of the key features added in DVB-T2 and their significance in the study of the system architecture. Then, this work continues with investigation of the performance of the signal under different transmission channels such as AWGN, Rayleigh fading and Rician fading channels. Subsequently, this study explores the different radar systems and its signals. Lastly, this research ends with investigation of method of recovering DVB-T2 signal from LFM signal. Suitable simulations for this study are carried out using CSP and MATLAB. The use of CSP is introduced to allow better understanding on the DVB-T2 system. It is used to simulate end-to-end DVB-T2 chain and signal performance of DVB-T2. The bit error rates at the output of the receiver end are collected. Finally, results obtained are discussed in this report.